Viability of wall-embedded tag antenna for ultra-wideband real-time suitcase localisation - Zaric, A.; Matos, V. S.; Costa, J. R.; Fernandes, C. A. (IET Microwaves, Antennas and Propagation, 2014)
Viability of a conformal single-layer monopole antenna is studied for a wall-embedded tag in an ultra-wideband (UWB) suitcase localisation application based on impulse radio UWB. The performance of the embedded antenna is simulated and confirmed experimentally in real-time localisation (RTL) experiments carried out in a cluttered laboratory environment. Evaluation in the main planes shows average suitcase positioning error around 8 cm for worst-case conditions. RTL tests are made when the suitcase is empty, when it is filled with common travelling items and also when it is shadowed by a second suitcase. A vector network analyser-based measurement set-up is used for target localisation error evaluation. Additionally, the same tests are repeated using portable commercial time-domain transceivers with similar results.